Chemosensitivity in the Sea Urchin Paracentrotus lividus (Echinodermata: Echinoidea) to Food-Related Compounds: An Innovative Behavioral Bioassay - Solari, Paolo; Pasquini, Viviana; Secci, Marco; Giglioli, Angelica; Crnjar, Roberto; Addis, Pierantonio (Frontiers in Ecology and Evolution, 2021)
Like other animals, echinoderms rely on chemical senses to detect and localize food resources. Here, we evaluate the chemical sensitivity of the sea urchin Paracentrotus lividus to a number of stimuli possibly related to food, such as a few sugars, compared to the blue-green algae Spirulina (Arthrospira platensis). To do this we developed a simple, innovative method based on the recording of “urchinograms” estimating the movements of spines, pedicellariae, tube feet, and eventually of the whole sea urchin, in response to chemicals, while keeping both the whole animal and the stimulus in their natural environment, underwater. Our results show that Spirulina is a highly stimulating compound for the sea urchin, by acting in a dose-dependent manner. The animals resulted also sensitive, even if to a lesser extent, to some sugars, such as the monosaccharide glucose, but not to its isomer fructose, while among disaccharides, they sensed cellobiose, but not sucrose or trehalose. From an applied point of view, any insight into the chemical sensitivity of sea urchins towards potential food-related compounds may lead to the discovery of key chemicals that would help improve the efficiency and reduce the costs of dietary substrates for optimization of intensive rearing strategies. Although this method has been developed for P. lividus, it will be suitable to evaluate the chemical sensitivity of other echinoderms and other marine invertebrates characterized by low mobility.